The rhythm makes you move - Rebekka Sól Þórarinsdóttir 2000- (2022)
In this thesis, I analysed two graduation pieces from the contemporary dance program in the Iceland University of the Arts, Phygital Glitch by Gígja Jónsdóttir and Run/trough by Katrín Gunnarsdóttir. I researched the different affects music had on these two dance pieces both in the processes of making them and in the performance. Then I will compare the two methods of incorporating music together and see how the music affected the movements. I both speak about my own experiences of the pieces and took a look at the methods of two artists, the choreographer and dancer Pina Bausch and the music composer Kristine Torgersen, that have both written about music and movement together. See how they view that relationship and how they have approached both music and movement in their creative processes. Dance and music are so related that I propose the question of, if it is possible to completely separate dance and music? In my research I have realised that it’s very difficult to take the music out of the dance, since the rhythm will still resonate in the movements and qualities of the dance even if the audible soundscape is removed. It’s possible to visualize the sound only from watching the style, quality and rhythm if the movements.